Impacto contable - tributario de la NIIF 9 en la cartera de créditos de los fondos complementarios previsionales cerrados del Ecuador, 2019. - Paredes Muñoz, Jimmy Armando (Machala : Universidad Técnica de Machala, 2022)
The Closed Complementary Pension Funds (FCPC) are non-profit entities in charge of solving the social security needs unsatisfied by public social security, so they must be profitable and sustainable over time to guarantee a decent retirement to their participants. The relevant documentation is developed through descriptive research, applying both theoretical and empirical scientific methods to determine the advantages offered by international financial reporting standards to this type of institution. The FCPCs are characterized by being parallel to the social security provided by the Ecuadorian Social Security Institute (IESS), formed at the initiative of its members protected by article 34 of the Ecuadorian Constitution; Its purpose is to improve the conditions of retirement upon retirement, to have a pension attached to the monthly payment of the public system, to grant financial services such as pledge, unsecured and mortgage loans in accordance with its statutes and competent regulations. The problem is the lack of knowledge about the accounting and tax impact of International Financial Reporting Standards (IFRS 9) in the credit portfolio of closed pension funds; especially, in the use of financial instruments to estimate credit risk, depreciation of fixed assets, criteria to measure profitability and administrative flexibility. State regulatory and control agencies apply national standards that are designed for for-profit entities with the intention of maximizing tax collection and taxes, being not very flexible for FCPCs. In the results, it can be seen that the application of IFRS 9 in the loan portfolio represents an improvement in terms of liquidity, reserve assets, liabilities and return on investments. By calculating its value based on the reasonableness of the balance; It allows adjusting interest rates, accruing operating expenses, venturing into new markets and adjusting benefits based on the number of participants and inducing new members by streamlining their financial instruments in parallel with the mechanisms used by the Superintendency of Banks.
Los Fondos Complementarios Previsionales Cerrados (FCPC) son entidades sin fines de lucro encargadas de solventar las necesidades en seguridad social insatisfechas por el seguro social público, de modo que deben ser rentables y sostenibles en función del tiempo para garantizar un retiro digno a sus partícipes. La documentación pertinente se desarrolla mediante una investigación de carácter descriptivo, aplicando métodos científicos tanto teóricos como empíricos para determinar las ventajas que ofrecen las normas internacionales de información financiera a este tipo de instituciones.Los FCPC’s se caracterizan por ser paralelos a la seguridad social brindada por el Instituto Ecuatoriano de Seguridad Social (IESS), formados por iniciativa de sus miembros amparados en el artículo 34 de la carta magna del Ecuador; su finalidad es mejorar las condiciones del retiro al jubilarse, tener una pensión anexa a la mensualidad del sistema público, otorgar servicios financieros como préstamos prendarios, quirografarios e hipotecarios acorde a sus estatutos y reglamentos competentes .La problemática es el desconocimiento sobre el impacto contable y tributario de las Normas Internacionales de Información Financiera (NIIF 9) en la cartera de crédito de los fondos previsionales cerrados; en especial, en el uso de los instrumentos financieros para estimar riesgo crediticio, depreciación de activos fijos, criterios al medir la rentabilidad y flexibilidad administrativa. Los organismos de regulación y control del estado, aplican las normas nacionales que son diseñadas para entidades con fines de lucro con la intención de maximizar la recaudación tributaria e impuestos, siendo poco flexibles para los FCPC’s. En los resultados, se aprecia que la aplicación de las NIIF 9 en cartera de créditos, representa una mejora en términos de liquidez, activos de reserva, pasivos y retorno de inversiones. Al calcular su valor en función de la razonabilidad del saldo; permite ajustar las tasas de interés, devengar gastos operativos, incursionar en nuevos mercados y ajustar los beneficios en base a la cantidad de partícipes e inducir a nuevos integrantes al dinamizar sus instrumentos financieros en forma paralela a los mecanismos empleados por la Superintendencia de Bancos.
Keywords: FONDOS COMPLEMENTARIOS PREVISIONALES CERRADOS; INSTRUMENTOS FINANCIEROS, NIIF 9